Multiband Cmos Power Amplifierwith Integrated High-Q Compact Inductor For Lora Application - Rawat, Arvind Singh (2023)
In the wide development of the Internet of Things (IoT), Machine-to-Machine (M2M), and biomedical applications in research and standardization, the spectrum of sub-GHz has received fresh attention. Long-range (LoRa) devices use the sub-GHz frequency bands to operate. The size of the chip becomes bigger when designed to target low frequencies and it is mainly contributed by the inductors. In this research, a high-performance CMOS power amplifier (PA) with a novel custom shape, high Qfactor compact inductor (HQCI) is fabricated in 130 nm, 6-metal layers CMOS process.